Unethical Leadership and Employee Extra-Role Behavior in Information Technology Sector: A Moderated Mediation Analysis - Zheng, Fengjiao; Khan, Naseer Abbas; Khan, Muhammad Waseem Abbas (Frontiers in Psychology, 2021)
During the COVID-19 pandemic, enterprises were obliged to employ social media and digital tools to complete ordinary work. The pandemic has created a series of complexities and challenges, which have hampered harmonic contact between leaders and followers. The indirect relationship between unethical leadership and Extra-role Behavior (EXB) via psychological empowerment is investigated in this study. We also look into the role of POS as a moderator in the link between unethical leadership and psychological empowerment, as well as the indirect link between unethical leadership and EXB. Data were obtained from 258 supervisor-employee dyads from various small and mid-sized information technology (IT) enterprises using time lag data. Unethical leadership has an impact on employee psychological empowerment as well as EXB. The findings of this study indicated that POS also mitigated the negative consequences of unethical leadership on employee psychological empowerment. Similarly, the role of psychological empowerment as a mediator in the link between unethical leadership and employee EXB is influenced by POS. This study will also benefit researchers and practitioners interested in human resource practices in the IT industry.